The Role Of Brand Awareness Mediates The Influence Of Social Media Marketing On The Purchase Intention Of Spotify Premium Services - Kadek Budi Indrayana; I Wayan Santika (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
Purchase intention is a form of consumer behavior that wishes to own a product based on the experience, use, and attractiveness of a product. Purchase intention arises because of stimuli that come from within consumers and provide encouragement or motivation to own a product. This study aims to examine the role of brand awareness in mediating the effect of social media marketing on the purchase intention of Spotify premium services for people in Denpasar City. The population of this study is people in Denpasar City who have never purchased Spotify premium services, the number of which is not known with certainty (infinite). The sample was determined using a non-probability sampling method with a purposive sampling technique. Data collection was carried out by distributing questionnaires to 108 respondents. The analysis techniques used are descriptive statistical analysis, classical assumption test, path analysis, Sobel test, and VAF test. The results showed that social media marketing has a positive and significant effect on purchase intention. Social media marketing has a positive and significant effect on brand awareness. Brand awareness has a positive and significant effect on purchase intention. Brand awareness is able to partially mediate and increase the total influence of social media marketing on purchase intention. The results of this study provide implications for marketing strategies, especially in company management can develop marketing strategies by paying attention to social media marketing indicators and brand awareness that have good performance in this study in order to increase the purchase intention of Spotify premium services.